A systematic review exploring palliative care for families who are forced migrants. (31st August 2020) - Clancy, Marie; Taylor, Julie; Bradbury‐Jones, Caroline; Phillimore, Jenny
Abstract: Aims: To explore the palliative care experiences of forced migrant children, families, and healthcare professionals (HCPs) highlighting successes, challenges, and associated practice implications. Design: Systematic literature review. Data Sources: The following search engines were searched from 2008 ‐ 2018: Allied and Complementary Medicine Database, Cumulative Index to Nursing and Allied Health, MEDLINE, Embase, ProQuest, Scopus, Psycinfo, and Web of Science. Extensive reference and citation checking were also conducted. Review Methods: Systematic review followed PRISMA guidelines with prepared PROSPERO registered protocol #CRD42019129200. English language qualitative, quantitative, or mixed methods studies were eligible for inclusion. Study quality was appraised using the Mixed Methods Appraisal Tool (MMAT). Results: Eighteen studies (reported in 20 articles) met the final inclusion criteria. Most focused on challenges to care provision. Thematic analysis following methods proposed by Braun and Clarke was undertaken. Five themes were identified: (a) divergence of beliefs and expectations; (b) communication; (c) navigating healthcare systems; (d) burdens and coping strategies; and (e) training and knowledge. A compassionate, collaborative approach with mutual respect crossed themes and was linked to high‐quality care. Conclusion: Forced migrant families have multiple needs including physical and emotional support and help in navigating complex systems. Professional interpreters can ease communication barriers when resourced appropriately. Individualized care is crucial to addressing the intricate mosaic of culture such families present. A cultural sensitivity/insensitivity framework is presented that may help guide future interactions and priorities for those working in children's palliative care. Impact: This systematic review explored the international experiences of palliative care for forced migrant families. The findings highlight the plight of families who experience multiple traumas and increased levels of grief and loss through their migration experiences and when caring for a child with a life‐limiting condition. This research has potential to have an impact on professionals working with culturally diverse families in all palliative care settings. 摘要: 目标: 探讨被迫移民儿童、家庭和医疗专业人员(HCP)的姑息治疗经验, 强调成功、挑战和相关实践意义。 设计: 系统文献回顾。 数据来源: 搜索2008年至2018年以下搜索引擎中的内容:英国联合补充医学数据库、CINAHL护理学全文权威数据库、联机医学文献分析和检索系统(MEDLINE), 荷兰医学文摘数据库(Embase)、ProQuest学位论文文摘索引数据库、Scopus电子数据库、心理学文摘(PsycINFO)和科学网。此外, 还进行了广泛的参考文献和引文检查。 评审方法: 系统回顾遵循PRISMA指南, 编制PROSPERO注册协议编号是CRD42019129200。入选标准为英语类的定性、定量或混合方法研究。采用混合方法评价工具(MMAT)评价研究的质量。 结果: 18篇研究(报告的有20篇)符合最终入选标准。最关注的是护理法规方面的挑战。采用布劳恩和克拉克提出的方法进行专题分析。确定了五大主题:(a) 信念和期望的分歧;(b)沟通;(c)医疗体系导航;(d)负担和应对策略;以及(e)培训和知识。依托跨主题的相互尊重的富有同情心的协作方式, 与高质量的护理相联系。 结论: 被迫移民家庭有多种需求, 包括身体和精神上的支持, 以及对于复杂体系导航的帮助。如果资源充足, 专业口译员可以缓解沟通上存在的障碍。个性化护理对于解决这些家庭所呈现的复杂多元文化至关重要。提出一个文化敏感性/不敏感性的框架, 可能有助于对从事儿童姑息治疗人员在其今后互动和工作要务方面给予指导。 影响: 本系统回顾探讨了国际上对被迫移民家庭进行姑息治疗的经验。研究发现强调那些经历了多重创伤的家庭困境, 在他们移民的经历中, 以及在照顾重症患者儿童时, 他们的悲伤和失落程度有所增加。该研究有可能对在所有姑息治疗环境中与多样文化家庭合作的专业人士产生影响。